2022
DOI: 10.1089/neur.2021.0072
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytes Are Not Required for Neurogenic Heterotopic Ossification Development after Spinal Cord Injury

Abstract: Neurogenic heterotopic ossifications (NHOs) are incapacitating complications of traumatic brain and spinal cord injuries (SCI) that manifest as abnormal bone formation in periarticular muscles. Using a unique model of NHO after SCI in genetically unmodified mice, we have previously established that the innate immune system plays a key driving role in NHO pathogenesis. The role of adaptive immune cells in NHO pathogenesis, however, remains unexplored in this model. Here we established that B lymphocytes were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…(17,19) Using this model, we have shown that monocytes/macrophages infiltrating the injured muscle are critical in promoting NHO development, (17) whereas granulocytes and lymphocytes are dispensable. (20,21) Further studies revealed that SCI drives a prolonged inflammatory response in injured muscles (22) with elevated and persistent expression of the inflammatory cytokines oncostatin M (OSM) and interleukin-1 (IL-1), which both promote NHO development. (22)(23)(24) Considering that IL-1 and OSM signaling are both key mediators of the inflammatory response to infections, (25)(26)(27) we hypothesized that the increased prevalence of NHO in patients with infections may be due to exacerbated inflammatory signaling in response to these infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(17,19) Using this model, we have shown that monocytes/macrophages infiltrating the injured muscle are critical in promoting NHO development, (17) whereas granulocytes and lymphocytes are dispensable. (20,21) Further studies revealed that SCI drives a prolonged inflammatory response in injured muscles (22) with elevated and persistent expression of the inflammatory cytokines oncostatin M (OSM) and interleukin-1 (IL-1), which both promote NHO development. (22)(23)(24) Considering that IL-1 and OSM signaling are both key mediators of the inflammatory response to infections, (25)(26)(27) we hypothesized that the increased prevalence of NHO in patients with infections may be due to exacerbated inflammatory signaling in response to these infections.…”
Section: Introductionmentioning
confidence: 99%
“…( 17,19 ) Using this model, we have shown that monocytes/macrophages infiltrating the injured muscle are critical in promoting NHO development, ( 17 ) whereas granulocytes and lymphocytes are dispensable. ( 20,21 ) Further studies revealed that SCI drives a prolonged inflammatory response in injured muscles ( 22 ) with elevated and persistent expression of the inflammatory cytokines oncostatin M (OSM) and interleukin‐1 (IL‐1), which both promote NHO development. ( 22‐24 )…”
Section: Introductionmentioning
confidence: 99%